Stratigraphy and structure of the Altar basin of NW Sonora: Implications for the history of the Colorado River delta and the Salton trough - Martín Pacheco; Arturo Martín-Barajas; Wilfred Elders; Juan Manuel Espinosa-Cardeña; Javier Helenes; Alberto Segura (Revista Mexicana de Ciencias Geológicas)
The Altar basin in northwestern Sonora, Mexico, is a subsidiary basin forming a now inactive part of the Colorado River delta. Its sedimentary record illustrates how the delta prograded in the last 4–5 Ma over a late Miocene, structurally distinct, marine basin at the northern end of the Gulf of California. Our interpretation of outcrop data, and data from seven exploratory wells, six analog seismic lines    of Petróleos Mexicanos (PEMEX), and magnetic and gravity surveys from various sources indicates the existence of three sedimentary sequences, A, B, and C, which can be correlated at regional scale and have a thickness >5 km at the basin depocenter. The lower sedimentary sequence A is a shale unit representing open marine conditions (outer neritic). It grades into a thick sequence of interstratified mudstone, siltstone, and sandstone (sequence B), which grades in turn into poorly consolidated sand (sequence C). Extensive outcrops of a sandy, cut and fill succession exposed along the coast of Sonora are consistent with sequences B and C being the sub-aqueous and the sub-aereal parts of the delta, respectively. A contact at the base of the sequence A, where pre-marine continental deposits are missing, and where the marine sequence overlies crystalline basement, is interpreted as tectonic transport along a top-to-the-northwest detachment fault. The Altar basin became inactive as result of the westward shift in the locus of tectonic activity from the Altar fault to the Cerro Prieto fault, coupled with realignments in the course of the Colorado River during Pleistocene time.